CVD Synthesis of Intermediate State-Free, Large-Area and Continuous MoS2 via Single-Step Vapor-Phase Sulfurization of MoO2 Precursor - Tinna Chiawchan; Harihara Ramamoorthy; Kanokwan Buapan; Ratchanok Somphonsane (My University, 2021)
The low evaporation temperature and carcinogen classification of commonly used molybdenum trioxide (MoO
Keywords: Molybdenum disulfide; Stoichiometry; Sublimation; 2D Materials and Applications